(untitled) (Iranian Journal of Kidney Diseases, 2014)
Isolated pleural involvement is rare in Kaposi sarcoma (KS). We report an unusual case of bloody pleural effusion and ascites associated with KS in a kidney transplant recipient. A 50-year-old man who had received kidney transplantation from a living unrelated donor presented with a massive left-side pleural effusion, ascites, and a skin lesion. The pleural effusion and ascites were bloody. The skin biopsy specimens showed KS infiltration (proliferation of spindle-shaped cells). Immunosuppressive therapy was discontinued. Although chemotherapy with paclitaxel was started, the patient died. To our knowledge, this is the first report of bloody pleural effusion and ascites associated with KS. Kaposi sarcoma can cause concomitant serositis in kidney transplant patients and should be considered as a differential diagnosis.